PENGUATAN KESADARAN LINGKUNGAN MAHASISWA BARU DALAM MENDUKUNG MITIGASI IKLIM GLOBAL - Rosyid, Abdul; Panuntun, Madina Dwi; Hasibuan, Dwi Kartika Asih; Zamani, Istiqomah Shariati; Purnama, Rizky; Tudon, Ifer Ehrlick (Jurnal AbdiMas Nusa Mandiri, 2026)
Climate change is a global issue and challenge that may have impacts in the future, thus requiring the strengthening of environmental literacy and awareness, particularly among the younger generation. This community service activity was aimed at new students of the Faculty of Forestry, Tadulako University, as educational partners in fostering an understanding of global climate change mitigation. The activity aimed to enhance participants’ knowledge, awareness, and commitment to the importance of climate change mitigation actions. The intervention was carried out through a public lecture featuring a speaker from the Green Institute, which included material presentation, interactive discussions, question-and-answer sessions, and reinforcement of sustainability values and the role of forests in climate change mitigation. This activity represents a form of community service intervention as it is oriented toward knowledge transfer, strengthening participants’ initial capacity, and fostering environmentally responsible attitudes. Post-activity evaluation was conducted using a descriptive quantitative approach through questionnaires. The evaluation results indicate that the public lecture, as an educational intervention in community service activities, had a positive initial impact on the target participants, with approximately 90% improvement in the knowledge dimension and 91% in the behavioral dimension. These findings suggest that public lectures contribute to strengthening climate literacy and fostering sustainable behavior within the university environment. This model can be replicated as an initial development approach for new students toward achieving a sustainable campus.